Mitochondrial and Y chromosome haplotype motifs as diagnostic markers of Jewish ancestry: a reconsideration - Tofanelli, Sergio; Taglioli, Luca; Bertoncini, Stefania; Francalacci, Paolo; Klyosov, Anatole; Pagani, Luca (Frontiers in Genetics, 2014)
Several authors have proposed haplotype motifs based on site variants at the mitochondrial genome (mtDNA) and the non-recombining portion of the Y chromosome (NRY) to trace the genealogies of Jewish people. Here, we analyzed their main approaches and test the feasibility of adopting motifs as ancestry markers through construction of a large database of mtDNA and NRY haplotypes from public genetic genealogical repositories. We verified the reliability of Jewish ancestry prediction based on the Cohen and Levite Modal Haplotypes in their “classical” 6 STR marker format or in the “extended” 12 STR format, as well as four founder mtDNA lineages (HVS-I segments) accounting for about 40% of the current population of Ashkenazi Jews. For this purpose we compared haplotype composition in individuals of self-reported Jewish ancestry with the rest of European, African or Middle Eastern samples, to test for non-random association of ethno-geographic groups and haplotypes. Overall, NRY and mtDNA based motifs, previously reported to differentiate between groups, were found to be more represented in Jewish compared to non-Jewish groups. However, this seems to stem from common ancestors of Jewish lineages being rather recent respect to ancestors of non-Jewish lineages with the same “haplotype signatures”. Moreover, the polyphyly of haplotypes which contain the proposed motifs and the misuse of constant mutation rates heavily affected previous attempts to correctly dating the origin of common ancestries. Accordingly, our results stress the limitations of using the above haplotype motifs as reliable Jewish ancestry predictors and show its inadequacy for forensic or genealogical purposes.